Ecological Issues in the Movie Entitled The Chronicles of Narnia: Prince Caspian - Nur Alfiah; Eva Solina Gultom (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2020)
This study aims to describe ecological issues based on the Ecocritical study of Greg Garrard in The Chronicles of Narnia: Prince Caspian movie by Andre Adamson. This study uses a qualitative descriptive method. The data in this study are dialogue, pictures, and texts in the movie that cover ecological issues. The data sources in this study were The Chronicles of Narnia: Prince Caspian movie by Andrew Adamson. The data is collected through the process of watching, enlisting, and screenshotting. The data is analyzed by identifying, classifying, and interpreting. The results of this study illustrate that in The Chronicles of Narnia: Prince Caspian movie there are ecological problems that occur due to human activities. Ecological problems were found in the movie are the relationship between human and nature, the animals become wild and extinct, destruction of nature. First, the relationship between human and nature shows that the characters of the female in the movie had associated with nature. Secondly, animals become wild and extinct because humans ignore the rights of animals. Such as destroying habitats and exploitation toward animals. Thirdly, the destruction of housing/shelter because of the human construction of houses for their own interests without thinking about other living things which is they take the land of Narnia.